Design of Flavonoid Microparticles with Channel Forming Properties to Improve Oxidative Stability of Sunflower Oil - Gimenez-Castillo, B (Wiley-VCH Verlag, 2017)
Quercetin (Q) and epicatechin (E) microparticles were designed using an oil-insoluble polymer (inulin [In]) as encapsulating agent and with or without an oil-soluble polymer (soy protein isolate [SPI]) by spray-drying. Encapsulation efficiencies were significantly higher for the E systems than for Q systems, suggesting that the spatial arrangement may affect the hydroxyl groups availability to form hydrogen bonds. The microencapsulated flavonoids were added to sunflower oil (SO) in order to evaluate its oxidative stability. The induction period (IP) of SO, determined in Rancimat at 60°C, significantly increased when Q-microparticles with or without SPI were added, showing those with SPI the highest IP value. In the case of E systems, the IP of SO increased only when E–In microparticles with SPI were added. These results suggest that SPI may favor the diffusion of flavonoids to the lipid medium by the formation of channels into the microparticles. The channels formation was observed for Q–In–SPI and E–In–SPI by a confocal laser scanning microscopy study. Additional oxidation studies under conditions of lower oxygen availability resulted in overall more retarded oxidation and no clear effect of SPI incorporation was observed. Practical application: The results show that it is possible to design flavonoid microparticles with antioxidant activity in bulk oils. The inclusion of a lipid-soluble polymer such as soy protein isolate in the microparticles favors the flavonoid release from the microparticles to bulk oil by channel formation. Epicatechin (E) and quercetin (Q) microparticles designed with inulin (IN, encapsulating agent) and soy protein isolate (SPI, channelizing agent) are incorporated to sunflower oil (SO). The channels formation is observed for Q–In–SPI and E–In–SPI by confocal laser scanning microscopy. The induction period (IP) of SO (Rancimat at 60°C) significantly increases when Q-microparticles with or without SPI are added, showing those with SPI the highest IP value. Regarding E systems, the IP of SO increases only when E–In microparticles with SPI are added. No clear effect of SPI incorporation is observed in additional oxidation studies under conditions of lower oxygen availability. © 2017 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim